A phenomenological approach to diagnosing psychosis in autism spectrum disorder and intellectual disability: a case series. Issue 2 (3rd April 2018) - Rai, Rahul; Tromans, Samuel; Kapugama, Chaya; Chester, Verity; Gunaratna, Ignatius; Langdon, Peter; Alexander, Regi T.
Abstract : Purpose: The diagnosis of psychosis in individuals with autism spectrum disorder (ASD) poses a unique clinical challenge. The presence of intellectual disability (ID) further complicates the diagnostic picture. Reliable and timely diagnosis of psychosis in such individuals minimises the duration of untreated psychotic symptoms and the subsequent impact on the quality of life of the patients concerned. The paper aims to discuss this issue. Design/methodology/approach: The authors present four patients with psychosis, ASD and ID, who have received care within forensic mental health and ID settings. These examples demonstrate the interaction between these conditions, as well as issues pertaining to diagnosis and management. Findings: In all four patients, sustained use of antipsychotic medication was objectively associated with an improvement in psychotic symptoms and quality of life. In instances where autistic phenomena were accentuated upon development of psychosis, such features returned to the baseline levels evident prior to the onset of psychosis. Practical implications: The discussion and related case examples could improve the understanding of the possibility of psychosis in individuals with ASD and ID, and increase awareness of this diagnostic possibility among healthcare professionals. Originality/value: This is the first published case series illustrating the challenges of diagnosing psychosis in individuals with ASD and ID.